Sex Differences in the Visuomotor Control of Obstacle Crossing When Walking Are Not Age Related. Issue 3 (June 2022) - Kunimune, Sho; Okada, Shuichi
To ensure stable obstacle crossing when walking, visual information is required two steps before reaching the obstacle. As possible age-related sex differences in visuomotor control have not been investigated, we assessed sex differences in obstacle crossing while walking, as examined by toe clearance (TC) and postural stability. Participants were 14 younger and 14 older adults (equal numbers of men and women) who wore goggles for visual field adjustment while obstacle crossing during gait. We manipulated three visual field occlusion conditions (total, lower, and no visual field occlusions) two steps before the obstacle and analyzed the TC of the lead limb, and the participants' step width and root mean square of trunk acceleration as indices of postural stability. We found a significant interaction between sex and visual condition in step width, with men showing larger step width values than women in all visual field conditions. Moreover, while women showed no step-width differences across visual field conditions, men had a larger step width with the lower visual field occluded than in the other visual conditions. We found no other significant sex differences. Our results suggest that men may be more dependent than women on the upper visual field for postural stability during obstacle crossing. Sex differences in visuomotor control were not affected by age.